Dietary Quercetin Increases Colonic Microbial Diversity and Attenuates Colitis Severity in Citrobacter rodentium-Infected Mice - Lin, Rui; Piao, Meiyu; Song, Yan (Frontiers in Microbiology, 2019)
Disturbed balance between microbiota, epithelial cells and resident immune cells within the intestine contributes to inflammatory bowel disease (IBD) pathogenesis. The Citrobacter rodentium-induced colitis mouse model has been well documented. This model allows the analysis of host responses to enteric bacteria and facilitates improved understanding of the potential mechanisms of IBD pathogenesis. The current study evaluated the effects of dietary 30 mg/kg quercetin supplementation on C. rodentium-induced experimental colitis in C57BL/6 mice. Following dietary quercetin supplementation, the mice were infected with 5 × 108 CFU C. rodentium, and the pathological effects of C. rodentium were measured. The results showed that quercetin alleviated the effects of C. rodentium-induced colitis, suppressed the production of pro-inflammatory cytokines, such as interleukin (IL)-17, tumour necrosis factor alpha and IL-6 (P < 0.05), and promoted the production of IL-10 in the colon tissues (P < 0.05). Quercetin supplementation also enhanced the populations of Bacteroides, Bifidobacterium, Lactobacillus and Clostridia and significantly reduced those of Fusobacterium and Enterococcus (P < 0.05). These findings indicate that dietary quercetin exerts therapeutic effects on C. rodentium-induced colitis, probably due to quercetin’s ability to suppress pro-inflammatory cytokines and/or modify gut microbiota. Thus, these results suggest that quercetin supplementation is effective in controlling C. rodentium-induced inflammation.